Pengaruh Digital Marketing, Kualitas Produk, Dan Brand Image Terhadap Keputusan Pembelian Pada Produk Scommer.Co Di Kota Metro - Japlani, Ardiansyah; Fuadi, Selamet; Yuliani, Dwi (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine :1). The influence of digital marketing on purchasing decisions. 2). The effect of product quality on purchasing decisions. 3) the influence of brand image on purchasing decisions, and 4) the simultaneous influence of digital marketing, product quality, and brand image on purchasing decisions.The population of this research is all consumers who have used Scommer.co products. The number of samples in this study were 97 respondents. The sampling technique used is accidental sampling. Data were collected by questionnaire. The test instruments used are validity and reliability tests. The analysis technique used is multiple linear regression. The results showed that: 1). Digital marketing has an effect on purchasing decisions. 2) product quality has an effect on purchasing decisions. 3) brand image has an effect on purchasing decisions. 4) digital marketing, product quality, and brand image have a simultaneous effect on purchasing decisions.